2001
DOI: 10.1200/jco.2001.19.10.2587
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Trastuzumab and Paclitaxel Therapy for Metastatic Breast Cancer With Analysis of Efficacy by HER2 Immunophenotype and Gene Amplification

Abstract: Weekly trastuzumab and paclitaxel therapy is active in women with metastatic breast cancer. Therapy was relatively well tolerated; however, attention to cardiac function is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
288
3
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(310 citation statements)
references
References 25 publications
13
288
3
6
Order By: Relevance
“…Although this agent is only active in a minority (30%) of Her-2 þ tumors, treatments that enhance the activity of Herceptin should improve therapeutic outcome for a greater number of Her-2 þ patients. [5][6][7][8][9][10] In this study, we have used the novel approach of combining a gene drug (Ad-mda7) with the biological agent, Herceptin, and evaluated its antitumor effects against breast cancer cells. Preliminary results of this study have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this agent is only active in a minority (30%) of Her-2 þ tumors, treatments that enhance the activity of Herceptin should improve therapeutic outcome for a greater number of Her-2 þ patients. [5][6][7][8][9][10] In this study, we have used the novel approach of combining a gene drug (Ad-mda7) with the biological agent, Herceptin, and evaluated its antitumor effects against breast cancer cells. Preliminary results of this study have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] In these studies, Herceptin has shown additive antitumor activity, and statistically significant survival benefit, and is now being integrated into the adjuvant and neoadjuvant setting. [5][6][7][8][9][10] Trastuzumab plus taxanes is the only combination indicated for the treatment of patients with MBC whose tumors overexpress Her-2 and as a single agent in women with Her-2-overexpressing MBCs resistant to chemotherapy. Although a subset of patients treated has shown cardiotoxicity, Herceptin is a generally well-tolerated drug and side effects that are commonly seen with chemotherapy are rarely observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the majority of patients who initially respond to Trastuzumab demonstrate disease progression within 1 year of treatment initiation. Combination of Trastuzumab with Paclitaxel (Seidman et al, 2001) or Docetaxel (Esteva et al, 2002) increase the response rate and overall survival.…”
Section: Naked Antibodiesmentioning
confidence: 99%
“…Targeting HER-2/neu with trastuzumab, a humanized anti HER-2/neu monoclonal antibody, inhibits the growth signals mediated by this oncogene [7]. Trastuzumab demonstrated moderate activity as single agent, but showed high activity in combination with chemotherapy as front-line therapy in HER-2/neu positive BC [8][9][10]. In a randomized trial of first-line therapy in HER-2/neu positive BC, the combination of trastuzumab with anthracyclines or taxanes significantly improved clinical outcome [11] and quality of life [12] as compared to chemotherapy alone.…”
Section: Introductionmentioning
confidence: 99%